2013
DOI: 10.1155/2013/864319
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Chronic Pain and Its Treatment

Abstract: This paper reviews the impact of genetic variability of drug metabolizing enzymes, transporters, receptors, and pathways involved in chronic pain perception on the efficacy and safety of analgesics and other drugs used for chronic pain treatment. Several candidate genes have been identified in the literature, while there is usually only limited clinical evidence substantiating for the penetration of the testing for these candidate biomarkers into the clinical practice. Further, the pain-perception regulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 219 publications
(166 reference statements)
0
15
0
1
Order By: Relevance
“…This article will describe CYP2D6 (cytochrome p450 2D6) and OPRM1 (μ1 opioid receptor), the most important gene coding, respectively, for a metabolizing enzyme and receptor for opioids (5)(6)(7)(8)(9)(10)(11). Integration of their variability in each patient allows for building a rational and scientific basis for personalized pain management ( Fig.…”
mentioning
confidence: 99%
“…This article will describe CYP2D6 (cytochrome p450 2D6) and OPRM1 (μ1 opioid receptor), the most important gene coding, respectively, for a metabolizing enzyme and receptor for opioids (5)(6)(7)(8)(9)(10)(11). Integration of their variability in each patient allows for building a rational and scientific basis for personalized pain management ( Fig.…”
mentioning
confidence: 99%
“…Medical literature provides several studies which have revealed that the polymorphism of inflammatory cytokine genes influences pain perception and analgesics dose. Furthermore, the altered levels of fatigue, depression and response to analgesics in pancreatic, lung or breast cancer have been described [15,[36][37][38][39][40][41][42][43]. These types of studies, however, have not been conducted for patients with multiple myeloma, though during the formation of bone destructions, anti-inflammatory cytokines are emitted by plasma cells and bone marrow stroma cells.…”
Section: Palliation For Painmentioning
confidence: 99%
“…Гены CYP3A4/CYP3A5 кодируют изофермент CYP3A4/5 цитохрома P450 печени, обеспечивающий метаболизм 50 % всех наркотических анальгетиков, включая фентанил. Вышеуказанные гены локализованы на хромосоме 7q22.1 и обеспечивают 3085 % вариабельности активности изофермента 3A4 [15]. Распределение известных одиночных нуклеотидных полиморфизмов (ОНП) гена CYP3A4 по скорости метаболических превращений представлено в табл.…”
Section: фармакогенетические аспектыunclassified